Minat Mahasiswa Berkarir Sebagai Auditor Pemerintah: Pengaruh Norma Subjektif, Marketability, dan Penghargaan Finansial - Aziza Ananta Putri; Halkadri Fitra (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of subjective norms, marketability, and financial rewards on career choice as external government auditors. The method used in this sampling is using purposive sampling technique. In this study, 166 UNP accounting students class 2018 and 2019. This study uses multiple regression analysis with the help of the SPSS application. The results of this study partially prove that subjective norms, marketability, and financial rewards have a positive effect on students' interest in a career as external government auditors. The limitations of this study are that there is only one object of this research, This study uses a survey method in the form of a questionnaire which allows respondents to fill in the questionnaire not seriously so that it can lead to misleading results, and his research is only limited to 3 factors this allows the neglect of other factors that have a greater influence on career choice as an external government auditor.